ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMP PADA MATERI FUNGSI KUADRAT - Siti Julaeha; Gida Kadarisma (IKIP Siliwangi, 2020)
Mathematical reasoning ability is an important ability in helping an individual, in this case the individual does not just remember facts, rules, and steps in solving problems, but reasoning is a skill in making predictions based on his experience. In this article, mathematical reasoning skills will be analyzed on the quadratic function material for grade IX Junior High School odd semester. The goal is to find out such as students' reasoning abilities in studying the quadratic function material. This research is a qualitative descriptive research method with the subject of 28 grade IX students at a junior high school in Cimahi, with various classifications including high, medium, and low-ability students. This is done by giving a test of 5 questions. Then the results are analyzed through data obtained from students' answers to the questions, so that it shows that the achievement of the test with reasoning skills shows that the results obtained by students are still below average.